Business Ethics Index: USA 2006 - Tsalikis, John (Journal of business ethics, 2007)
This study continues the systematic measurement of consumers’ sentiments toward business ethical practices first measured in 2004. The Business Ethics Index (BEI) comprises the four measurements representing the dimensions of “personal–vicarious” and “past–future”. A professional telephone interviewing company was hired to collect five consecutive waves of 1045 telephone interviews in an omnibus procedure. The collection of the five waves represented a sampling process which enables the creation of confidence intervals for this, and subsequent, measurements of the BEI. The overall BEI fell to 102.6 (from a revized 108.7 in 2004). The drop was attributed to a fall in consumer expectations of the future ethical behavior of business.